Antônio Rodrigues Bello : as bases da pintura de falsa arquitetura na capitania do ouro no século XVIII - Tiago da Cunha Rosa (2022)
This study focuses on the Portuguese painter Antônio Rodrigues Bello, who worked in the region of Cachoeira do Campo, a village of Ouro Preto, around the year of 1750. This painter performed an ancient quadratura painting on the ceiling of the Capela-mor da Matriz de Nazaré, which is documented and morphologically framed among the oldest ones in the region, besides a series of other works throughout the temple.In this sense, this study delves into the painter’s work of art in the Cachoeira do Campo’s temple by initially investigating aspects of the aforementioned quadratura carried out by him, which is, currently, covered by a new pictorial layer, and, afterward, by analyzing and comparing it to other quadraturas in the region, especially those in the Capela de Bom Jesus das Flores do Taquaral, in Ouro Preto, which is believed to be directly related to his work.The quadraturas hereby analyzed, demonstrate, together, the predominance of a certain compositional method in the region of Vila Rica during the first half of the 18th century, which, since they distance from pre-established treaty solutions, they indicate the adoption of their own. These solutions might provide evidence of the core of the perspective paintings work in Minas Gerais.